Ultra Sonographic Measurement of Placental Thickness during Pregnancy as a Parameter for Estimating Gestational Age of the Fetus - Shamoona Rashid, Uzma Mumtaz, Ayesha Naeem, Sadia Hanif, Amna Khalid, Madiha Bangash, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most effective prenatal care and successful births are always dependent on accurate gestational age estimation (GA). The gestational age play important role in biochemical tests interpretation. Objective: The study was carried out to find the ultra-sonographic measurements done to check the placental thickness. It is an important factor for the gestational age estimation. Study design: This is a cross-sectional study conducted at Al Nafees Medical College and Hospital, Islamabad for the duration of one year from June 2021 to May 2022. Material and Methods: The study was conducted on 325 pregnant women that visited tertiary care unit for a period of one year. All women were fully aware of the study and written consent was taken from them. Results: the thickness of placenta found at different gestational age. From 15 to 39 weeks of gestation the data was collected and no. of cases having placental thickness were recorded. Maximum and minimum placental thickness in mm was measured and average was taken. The age range of the women was 18-36 years. The 26 years was the mean age. The statistical significance was found by SPSS tool Conclusions: In this study there was found a strong link between week of gestational age and thickness of placenta. Placental thickness along with other parameters were studied in each week by ultrasound and the results were analyzed. In case where the exact duration of pregnancy is unknown, placental thickness can give information about age of fetus and other features like intrauterine stunted growth. Keywords: Placental thickness and gestational age.